Bright air black - Vann, David (Black Cat, 2017)
"Following the success of Aquarium which was a New York Times Editor's Choice and garnered numerous rave reviews, David Vann transports us to 13th century B.C. to give a nuanced and electric portrait of the life of one of ancient mythology's most fascinating and notorious women, Medea. In brilliant poetic prose Bright Air Black brings us aboard the ship Argo for its epic return journey across the Black Sea from Persia's Colchis--where Medea flees her home and father with Jason, the Argonauts, and the Golden Fleece. Vann's reimagining of this ancient tale offers a thrilling, realist alternative to the long held notions of Medea as monster or sorceress. We witness with dramatic urgency Medea's humanity, her Bronze Age roots and position in Greek society, her love affair with Jason, and her tragic demise. Atmospheric and spellbinding, Bright Air Black is an indispensable, fresh and provocative take on one of our earliest texts and the most intimate and corporal version of Medea's story ever told"--